2005
DOI: 10.1002/polb.20641
|View full text |Cite
|
Sign up to set email alerts
|

The influence of confinement and curvature on the morphology of block copolymers

Abstract: In the bulk, at equilibrium, diblock copolymers microphase separated into nanoscopic morphologies ranging from body-centered cubic arrays of spheres to hexagonally packed cylinders to alternating lamellae, depending on the volume fraction of the components. However, when the block copolymers are forced into cylindrical pores, where the diameter of the pores are only several repeat periods of the copolymer morphology or less, then commensurability of the copolymer period and the pore diameter can impose a frust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
168
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(173 citation statements)
references
References 35 publications
5
168
0
Order By: Relevance
“…When the pore diameter is reduced to a size comparable to the bulk period (D/L 0 =0.92~2.2), a rich variety of morphologies, not seen in the bulk, were observed that included stacked torus-like morphologies and single-, double-, and triple-helical morphologies [10,11]. Similarly, for the sphere-forming PS-b-PB, one observes that large pores (D/L 0 > 3.2) lead to spherical PB domains aligned along the pore axis, whereas in pores with smaller diameters (D/L 0 < 3.2), core-shell cylindrical morphologies, single columns of spherical microdomains, and spirals of doubly and triply paired spherical microdomains are observed [9,10]. Helical and stacked toroidal structures have also been observed by Wang and coworkers in the study of asymmetric poly(styrene-b-2-vinylpyridine) DBCPs confined in anodic aluminum oxide nanopores [12].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…When the pore diameter is reduced to a size comparable to the bulk period (D/L 0 =0.92~2.2), a rich variety of morphologies, not seen in the bulk, were observed that included stacked torus-like morphologies and single-, double-, and triple-helical morphologies [10,11]. Similarly, for the sphere-forming PS-b-PB, one observes that large pores (D/L 0 > 3.2) lead to spherical PB domains aligned along the pore axis, whereas in pores with smaller diameters (D/L 0 < 3.2), core-shell cylindrical morphologies, single columns of spherical microdomains, and spirals of doubly and triply paired spherical microdomains are observed [9,10]. Helical and stacked toroidal structures have also been observed by Wang and coworkers in the study of asymmetric poly(styrene-b-2-vinylpyridine) DBCPs confined in anodic aluminum oxide nanopores [12].…”
Section: Introductionmentioning
confidence: 92%
“…[6] Various novel and sometimes complex structures have been observed or predicted for block copolymers confined in cylindrical pores. Experimentally, Russell and coworkers carried out a series of studies on symmetric (bulk lamella-forming) [7][8][9][10] and asymmetric (bulk cylinder-and sphere-forming) [8][9][10][11] poly(styrene-b-butadiene) (PS-b-PB) DBCPs confined in cylindrical nanopores in alumina membranes. For the lamellaforming symmetric PS-b-PB, a set of curved, cylindrical lamellae parallel to the pore axis (called "concentric lamellae", CL) were observed when the pore diameter D is much larger than the bulk equilibrium period L 0 .…”
Section: Introductionmentioning
confidence: 99%
“…For the infiltrated samples, the total mass (block copolymer plus AAO template) was 25 mg, while the block copolymer mass was approximately 0.5 mg according to TGA experiments. The results were compared with those obtained with PE-b-PS neat samples at the same scanning rates and employing a mass of 2 mg. 40 60 Figure 5: DSC cooling scans at 30 ÂșC/min for the indicated samples before and after infiltration within AAO 60 nm templates.…”
Section: Pe Block Ps Blockmentioning
confidence: 99%
“…15,16 Similarly, thickness and surface interactions of ultrathin polymer films (the film thickness is in the order of 2R g of a polymer chain, or less) highly influence their glass transition and melting temperatures, [17][18][19] polymer dynamics in the glassy state, 20 crystallization kinetics and degree of crystallinity, [21][22][23] phase behavior, 24 and morphology. 25,26 For all the above examples, the portion of ''surface material'' is comparable with the bulk, due to extremely small object size, therefore, the ansatz claiming ''nano-object ÂŒ bulk ĂŸ surface'' seems relevant for such systems from a physical point of view. However, in certain experimental systems, 27,28 the size-dependent behavior of nanofibers bearing considerably higher transversal size ($500 nm) refute the size-dependence ansatz and require additional expressions to explain their behavior.…”
mentioning
confidence: 99%